Effect of waves on cavitation and pressure pulses. (October 2016) - Taskar, Bhushan; Steen, Sverre; Bensow, Rickard E.; Schröder, Björn
Highlights: KVLCC2 propeller has been analyzed in different wake distributions in presence of waves. Effect of wake change, ship motions, RPM variation and speed loss has been studied. Significant increase in pressure pulses was observed due to wake change in waves. It is found that having a wake data in waves could be beneficial for designing a propeller. Abstract: In view of environmental concerns, there is increasing demand to optimize the ships for the actual operating condition rather than for calm water. Now, in order to apply this for propeller design, a first step would be to study the effects of waves on propeller operation. Therefore, the aim of this paper is to identify and quantify the effect of various factors affecting the propeller in waves. The performance of KVLCC2 propeller in the presence of three different waves has been compared with calm water performance. Changes in performance in terms of cavitation, pressure pulses, and efficiency have been studied. Significant increase in pressure pulses has been observed due to wake change in waves even though cavitation did not show any significant change. An analysis using cavitation bucket diagram in different wave conditions indicates that a propeller optimized for calm water wake may perform much worse in the presence of waves. Therefore, having wake variation at least in critical wave conditions (where the wavelength is close to ship length) in addition to calm water wake could be very useful to ensure that the propeller performs equally well in the presence of waves.